Epidemiology of Cases of Suicide due to Hanging who Referred to Forensic Center of Shahriar in 2011 - Alimohammadi, AM; Mehrpisheh, Sh; Memarian, A (International Journal of Medical Toxicology and Forensic Medicine, 2013)
Background:Around 800,000 to a million people die by suicide every year, making it the 10th leading cause of death worldwide. According to high rates of suicide and hanging and death due to these reasons in the world and also in Iran,this study was conducted to evaluate cases of suicide by hanging. Methods: This descriptive cross-sectional study was conducted on 79 cadavers in forensicdissection centerof Shahriar in 2011. Necessary information including age, sex, laryngeal bone fracture, bleeding of soft tissue, number of family members, educational level, marital status, history of depression, addiction, smoking, history of any special disease, location of hanging, leaving any note, ethnicity and suicide intensity was entered in the checklist and were analyzed. Results:The mean age of cases was 33.4 (SD=13.62) years. 63 (79.7%) were male and 16 (20.3%) were female.10 (12.7%) patients of the study population were illiterate and 56 (78.9%) were under diploma and only 8 (11.3%) patients had diploma. 17 (23.9%) were unemployed, 5 (7%) were students, 20 (28.2%) were workers, 10 (14.1%) were employees and 15 (21.1%) were self-employment. 23 patients (32.4%) were drug addict. 13 patients (18.3%) had a history of depression. 38 patients (53.5%) were smokers. 56 (78.9%) of hanging were in home and 15 (21.1%) were in outdoors. Suicidal impulses in 33 patients (46.5%) was unspecified, in 10 cases (14.1%) was substance abuse, in 11 (15.5%) was mental disorders, in 6 patients (8.5%) was family problems, and in 7 patients (9.9%) was unemployment. Conclusion:Given the high rate of suicide, it is necessary to identify the risk factors, to prevent to the extent possible. Treatment of drug and alcohol addiction, depression, and those who have attempted suicide in the past may also be effective. Economic development through its ability to reduce poverty may be able to decrease suicide rates. Efforts to increase social connection especially in elderly males may be effective.